Analyzing the Interplay of School Culture and Teacher Communication in Enhancing School Effectiveness through Parental Involvement: A Bibliometric Study - Raden Bambang Sumarsono; Agus Timan; Sunarni Sunarni; Dedi Prestiadi; Suhari Muharam; Athalla Nauval Bhayangkara; Mochammad Ja'far Amri Amanulloh; Endra Ubaidillah (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This research examines trends in published works on school cultural openness and teacher communication skills, specifically how they contribute to enhancing school effectiveness when parents are actively involved. We aimed to chart citation patterns within Scopus and Google Scholar, identifying both key research themes and fresh insights through bibliometric data. Starting with 2086 initial records, we carefully selected 124 articles directly relevant to our inquiry. To achieve our research goals, we conducted a descriptive analysis of publication and citation trends from 2015 to 2025 using Excel, and also performed a citation analysis to identify the most influential authors. Additionally, a VOSviewer-based keyword co-occurrence analysis helped us visualise topic clusters and their relationships, revealing dominant themes and the direction research is moving. The results demonstrate a strong link between a school's open culture, teachers' communication skills, and improved school dynamics, particularly with active parent involvement. This makes a significant theoretical contribution to Education, underscoring the importance of prioritising inclusive, culturally responsive communication and structured parent engagement in school policies and programs. Our research also points out that the integrated connection between school cultural openness and teacher communication in enhancing school effectiveness through parent involvement is rarely discussed comprehensively. Therefore, we propose parental involvement as a moderating variable that can strengthen this relationship. It also opens avenues for future research that are more integrative and consider various contexts, aiming to create learning environments that are both inclusive and competitive.